Human Capital and Macroeconomic Growth: Austria and Germany 1960-1997. An Update - Dalia Marin; Reinhard Koman (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2005)
In an influential paper Mankiw, Romer, and Weil (1992) argue that the evidence on the international disparity in levels of per capita income and rates of growth is consistent with a standard Solow model, once it has been augmented to include human capital as an accumulable factor. In a study on Austria and Germany we augment the Solow model to allow for the accumulation of human capital. Based on a perpetual inventory estimation procedure we construct an aggregate measure of the stock of human capital of Austria and Germany by weighting workers of different schooling levels with their respective wage income. We obtain an estimate of the wage income of workers with different schooling from a Mincer type wage equation which quantifies how wages change with years of schooling. We find that the time series evidence on Austria and Germany is not consistent with a human capital augmented Solow model. Factor accumulation (broadly defined to include human capital) appears to be less (and not more) able to account for the cross-country growth performance of Austria and Germany when human capital accumulation is included in the analysis. Our results indicate that differences in technology are a driving factor in understanding cross country growth between these two neighboring countries with similar political and institutional background.
urn:nbn:de:bvb:19-epub-569-5
Keywords: O1; O3; O4; 330; Economic growth; total factor productivity; human capital; technical change; growth accounting